Parental adjustment to disability, stress indicators and the influence of social support. - Felizardo, Sara (2017)
Problem Statement: This study intends to understand the differences in parental stress and social support among parents groups of children with different disabilities in the context of parental adjustment to disability. Research Questions: There are significant differences in the results of stress and social support among parents groups of children with different disabilities, in order to improve intervention strategies with families? Purpose of Study: Parental adjustment to disability relates to the effectiveness with which families use the resources of their social network. We intend to analyze stress and social support differences among groups of parents of children with different disabilities and clarify relationships between the variables in order to suit family intervention strategies. Research Methods: A comparative research of descriptive correlational nature was undertaken. The sample of convenience included 152 parents of children with different disabilities (82 with intellectual disability; 37 with motor problems; 33 with autism) supported by institutions the Viseu municipality. The gathering instruments were: Parenting Stress Index - Portuguese version (Abidin & Santos, 2003), Social Support Questionnaire and Parental Questionnaire. Findings: The results revealed significant differences between groups of parents in the partial results of parental stress, specifically in the subscales Hyperactivity, Acceptance and Adaptation Flexibility (Child Domain), as well as subscale Paper Restriction (Parental Domain). With respect to social support, we found differences in the extent and availability of social support network. Conclusions: Knowing the specific dimensions of parental functioning, as well as aspects of social support, allows us to design intervention strategies targeted to the family needs and resources, promoting the quality of the parenting exercise and a better parental adjustment to disability.